Growing Cauliflower in Winter under Passive Solar Greenhouse in Trans Himalayan Ladakh, India - Angmo, Phunchok; Dolma, Tsering; Katiyar, Anand K; Chaurasia, O. P.; Stobdan, Tsering (Defence Life Science Journal, 2020)
Traditionally cauliflower is not grown during winter months in the trans-Himalayan Ladakh region due to sub-zero degree celsius at night. Accordingly, the feasibility of growing cauliflower, a temperature-sensitive crop, was studied during winter months in a passive solar greenhouse in the high altitude (elevation 3340 m) trans-Himalayan Ladakh region. Studies were conducted during 2017-2020 with three commercial varieties. Curd was formed in all the varieties despite the temperature extremes (0.0±1.6 to 39.5±0.9 ºC) in the greenhouse. Harvesting was done in the month of February. The mean marketable curd weight ranged from 258±113 to 743±62 g depending on variety and year, which suggested that cauliflower can be successfully grown during winter months in the trans-Himalaya. However, the marketable curd weight was significantly lower as compared to the yield potential of the varieties. High temperature inside the greenhouse resulted in the occurrence of fuzziness, and it ranged from 0-35% of the harvested curd depending on the year and variety. Fuzziness was not observed in cv Shentha while 10.4-35% of cv Amazing exhibited fuzziness.